2010
DOI: 10.1143/jjap.49.03cd02
|View full text |Cite
|
Sign up to set email alerts
|

4.0-inch Active-Matrix Organic Light-Emitting Diode Display Integrated with Driver Circuits Using Amorphous In–Ga–Zn-Oxide Thin-Film Transistors with Suppressed Variation

Abstract: We have newly developed a 4.0-in. quarter video graphics array (QVGA) active-matrix organic light-emitting diode (AMOLED) display integrated with gate and source driver circuits using amorphous In–Ga–Zn-oxide (IGZO) thin-film transistors (TFTs). Focusing on a passivation layer in an inverted staggered bottom gate structure, the threshold voltage of the TFTs can be controlled to have “normally-off” characteristics with suppressed variation by using a SiO x layer formed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…Silicon oxide (SiO x ), deposited by plasma-enhanced chemical vapor deposition (PE-CVD), is commonly used as an ES layer for a-IGZO TFTs, since the hydrogen content of SiO x is lower than that of hydrogenated silicon nitride (SiN x :H) deposited by PE-CVD [9]- [13]. However, even for the case of the SiO x ES layer deposited by PE-CVD, a certain amount of hydrogen also diffuses from the ES layer into the a-IGZO channel [14]. It has been reported that hydrogen strongly affects the electrical properties and stability of a-IGZO TFTs.…”
Section: Quantitative Analysis Of the Effect Of Hydrogenmentioning
confidence: 99%
“…Silicon oxide (SiO x ), deposited by plasma-enhanced chemical vapor deposition (PE-CVD), is commonly used as an ES layer for a-IGZO TFTs, since the hydrogen content of SiO x is lower than that of hydrogenated silicon nitride (SiN x :H) deposited by PE-CVD [9]- [13]. However, even for the case of the SiO x ES layer deposited by PE-CVD, a certain amount of hydrogen also diffuses from the ES layer into the a-IGZO channel [14]. It has been reported that hydrogen strongly affects the electrical properties and stability of a-IGZO TFTs.…”
Section: Quantitative Analysis Of the Effect Of Hydrogenmentioning
confidence: 99%
“…[1][2][3] Oxide-based TFTs have superior advantages because of their high field-effect mobility, 4 excellent uniformity, lowprocessing temperature, 5 and transparency in the visible light. 6 Film properties of oxide materials are drastically influenced by deposition methods and conditions.…”
mentioning
confidence: 99%
“…During the passivation SiO x layer deposition by PECVD, the plasma causes damage at the a-IGZO/insulator interface since the a-IGZO film is very thin ͑30 nm͒. 10 Therefore, these inferior electrical properties can be attributed to the extra interface states generated during the SiO x deposition process. Figures 2͑a͒ and 2͑b͒ show the illuminated transfer characteristics in a vacuum for the devices without and with SiO x passivation, respectively.…”
mentioning
confidence: 99%